1998
DOI: 10.1002/(sici)1521-186x(1998)19:6<377::aid-bem5>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to static magnetic fields on the morphology and morphometry of mouse epididymal sperm

Abstract: Morphologic and morphometric sperm characteristics of mouse epididymal extracts from animals exposed to static magnetic fields were evaluated. For this purpose, animals were exposed for 35 days to a field of 0.7 T generated by a commercial permanent magnet for either 1 or 24 h per day. The values of morphometric parameters were obtained using the morphometric module of the Sperm Class Analyzer® computerized image analysis system, and percentages of abnormalities were calculated. The size of sperm heads was una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 21 publications
(4 reference statements)
3
25
0
1
Order By: Relevance
“…There are few studies evaluating the effect of environmental condition and nutrition on sperm morphometry. Tablado et al (1998) evaluated the effect of exposure to static magnetic fields on sperm morphometric characteristics in the mouse, observing no significant alterations in sperm head morphometry. Maroto-Morales et al (2010) described significant differences in sperm head morphometry between rams belonging to different herds.…”
Section: Factors Affecting Sperm Morphometrysupporting
confidence: 84%
See 1 more Smart Citation
“…There are few studies evaluating the effect of environmental condition and nutrition on sperm morphometry. Tablado et al (1998) evaluated the effect of exposure to static magnetic fields on sperm morphometric characteristics in the mouse, observing no significant alterations in sperm head morphometry. Maroto-Morales et al (2010) described significant differences in sperm head morphometry between rams belonging to different herds.…”
Section: Factors Affecting Sperm Morphometrysupporting
confidence: 84%
“…This effect has been described in boars (Kondracki et al, 2005), dogs (Castro-López et al, 2008) and rams (Marti et al, 2011b). In addition, the final sperm morphology is defined during the pass through the epididymides, where maturation of the cells involves changes in the membrane composition, DNA package level, and acrosome structure (Yeung et al, 1997;Tablado et al, 1998;Gago et al, 2000;Soler et al, 2000). Another morphological characteristic affected by epididymal maturation process is the presence of cytoplasmic droplets (Cooper, 2011).…”
Section: Factors Affecting Sperm Morphometrymentioning
confidence: 99%
“…Slight changes in spermatogenesis and embryogenesis in mice exposed to 1.5T for 30min have been reported (Narra et al, 1996). The maturation of sperm movement in mice as well as postnatal testicular and epididymis development were largely unaffected by either single, short-term exposure or continuous, long-term exposure at 500-700mT (Tablado et al, 1996;Tablado et al, 1998;Tablado et al, 2000).…”
Section: Nematodes Mutant For Developmental and Aging Genes Are Resismentioning
confidence: 99%
“…By the way, Tablado et al (1998) found that the size of sperm heads and the percentage of sperm with coiled tails or of sperm with abnormal mid-piece or tail were unaffected in mice exposed to a 0.7 T commercial permanent magnet. We have previously reported the lack of alterations on morphological characteristics of male germ cells in mice exposed to a 60 Hz and 2.0 mT magnetic fields (Heredia-Rojas et al, 2004).…”
Section: Discussionmentioning
confidence: 99%